Postcolonial theory and international relations a critical introduction - Seth, Sanjay, 1961- (London ; New York : Routledge, 2013)
'Postcolonial theory has had the most impact in disciplines such as literature and, to some degree, history, and perhaps the least impact in the discipline of politics. However, there is growing interest in postcolonial theory within politics, and interest in especially high in the subfield of international relations. This text provides a comprehensive survey of how postoclonial theory shapes our understanding of international relations'--
pt. 1. Critique -- pt. 2. Performance.
Includes bibliographical references (p. [183]-199) and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: International relations -- Philosophy; Postcolonialism; Electronic books